Endoscopic Instruments and Electrosurgical Unit for Colonoscopic Polypectomy - Hong Jun Park (Korean Society of Gastrointestinal Endoscopy, 2016)
Colorectal polypectomy is an effective method for prevention of colorectal cancer. Many endoscopic instruments have been used for colorectal polypectomy, such as snares, forceps, endoscopic clips, a Coagrasper, retrieval net, injector, and electrosurgery generator unit (ESU). Understanding the characteristics of endoscopic instruments and their proper use according to morphology and size of the colorectal polyp will enable endoscopists to perform effective polypectomy. I reviewed the characteristics of endoscopic instruments for colorectal polypectomy and their appropriate use, as well as the basic principles and settings of the ESU.